Ultrathin Dielectric Perfect Absorber: Large‐Area Low‐Cost Dielectric Perfect Absorber by One‐Step Sputtering (Advanced Optical Materials 9/2019). Issue 9 (3rd May 2019) - Wang, Shaowei; Chen, Feiliang; Ji, Ruonan; Hou, Mingming; Yi, Fei; Zheng, Weibo; Zhang, Tao; Lu, Wei
Abstract : Shaowei Wang, Wei Lu and co‐workers (article number1801596 ) have developed an ultrathin perfect absorber with a dielectric plasmonic nanocomposite (TiN@AlN) and antireflective coating. The absorptivity is ultra‐high with average photon escaping rate of only 0.4% in the whole visible range, which is especially suitable for harvesting solar energy and eliminating stray light. It can be fabricated by a low‐cost one‐step sputtering approach in a very large area (200 mm × 200 mm for demonstration) on almost any substrates, even for flexible ones.